Knowledge, attitude and perception of COVID-19 among orthopaedic surgeons - Pradhan, Nabees Man Singh (Journal of Patan Academy of Health Sciences, 2020)
Introduction: COVID-19 has a long incubation period, is highly contagious but lacks definite cure. It has evolved into a pandemic resulting in global outcry. Preventive measures include hand washing or sanitization, maintaining social distance, face mask, quarantine etc. Orthopaedic surgeons are considered a high-risk group, due to the aerosol generating procedures (AGPs) they need to perform. A good knowledge and attitude are essential to prevent the contraction and spread of the virus.Method: This is a cross-sectional descriptive study done in the form of online survey via e-mail among the registered Orthopaedic surgeons of Nepal. A four-point Likert scale was used for single option answer. Ethical approval was obtained. Descriptive analysis of data was performed by Microsoft Excel.Result: Out of 123 responses, on the main issues regarding hand washing, social distancing and face masks, majority (>85%) of the Orthopaedicians had a good knowledge and attitude. Around 14% disagreed on Orthopaedic surgeries being AGPs. Majority (>90%) had a positive perception about implementation of preventive measures. More than 90% of the respondents believed that hospital meetings/teaching learning activities/presentations can be effectively conducted through virtual platforms.Conclusion: Study found that most Orthopaedic surgeons have good knowledge and attitude regarding COVID-19. Importance of hand hygiene, social distancing, surgical mask, and well-ventilated rooms were well understood. Most perceived AGPs is a high risk procedure. Study found need of awareness on doffing of PPE. Online platforms were felt effective for most meetings and clinical consultations.